2014
DOI: 10.1186/1471-2350-15-51
|View full text |Cite
|
Sign up to set email alerts
|

Exome sequencing identifies a novel mutation in PIK3R1 as the cause of SHORT syndrome

Abstract: BackgroundSHORT syndrome is a rare autosomal dominant condition whose name is the acronym of short stature, hyperextensibility of joints, ocular depression, Rieger anomaly and teething delay (MIM 269880). Additionally, the patients usually present a low birth weight and height, lipodystrophy, delayed bone age, hernias, low body mass index and a progeroid appearance.Case presentationIn this study, we used whole-exome sequencing approaches in two patients with clinical features of SHORT syndrome. We report the f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
28
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 33 publications
(29 citation statements)
references
References 14 publications
1
28
0
Order By: Relevance
“…The patients presented with other features: three patients had cardiac abnormalities (2/3 pulmonary stenosis and 1/3 ventricular septal defect) (3,7,8). Five patients also presented with sensorineural deafness [new patients 1, 2 and 7; (3)] (Table S1).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The patients presented with other features: three patients had cardiac abnormalities (2/3 pulmonary stenosis and 1/3 ventricular septal defect) (3,7,8). Five patients also presented with sensorineural deafness [new patients 1, 2 and 7; (3)] (Table S1).…”
Section: Resultsmentioning
confidence: 99%
“…Autosomal dominant inheritance has been confirmed by the identification of heterozygous mutations in PIK3R1 (MIM171833) as the cause of SHORT syndrome . A total of seven different mutations were reported in 24 individuals with SHORT syndrome, and highlighted a recurrent substitution (p.Arg649Trp) . PIK3R1 codes for the regulatory subunits of the phosphatidyl inositol‐3 kinase of class IA (PI3K) and is involved in activation of the AKT/mTOR pathway to ensure proper growth and cell proliferation .…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The medical ethics committee of the Hospital Universitario Central de Asturias, in compliance with the Helsinki Declaration, approved the study protocol. To identify the genetic cause of these patients' syndrome, we first performed exome sequencing analysis as previously described 20. To this aim, a Qiagen kit was used to extract genomic DNA from peripheral blood leucocytes following the manufacturer's instructions (QIAGEN, Germany).…”
Section: Methodsmentioning
confidence: 99%
“…Subsequent evaluation of additional patients revealed other prominent features, including partial lipodystrophy, with a selective reduction in subcutaneous adipose tissue in the face, flank, and buttocks, as well as marked insulin resistance (7,8). Recently, we and others have shown that the SHORT syndrome is associated with mutations in the Pik3r1 gene that encodes p85α (11)(12)(13)(14)(15). Most mutations cluster in the region encoding the C-terminal SH2 domain of p85α that is essential for binding of PI3K to tyrosine phosphorylated proteins, such as insulin receptor (IR) substrate-1 (IRS-1) and many growth factor receptors (11,12,14,15).…”
Section: Introductionmentioning
confidence: 99%